Pengaruh Pelatihan Siaga Bencana Gempa Bumi Terhadap Kesiapsiagaan Anak Usia Sekolah Dasar Dalam Menghadapi Bencana Gempa Bumi Di “Yayasan Hidayatul Mubtadiin Kediri - Sri Haryuni (Akademi Keperawatan Dharma Husada Kediri, 2018)
Natural disaster preparedness in schools or madrassas important because of the hours of the lessons is a gathering place for students certainly have a high vulnerability. If it does not do disaster risk reduction efforts, the school or madrasah at high risk would cause many casualties and damage, quantitatively as much as 75% of schools in Indonesia are at risk of moderate to high hazard. The purpose of this study to determine whether there are effects of the earthquake disaster preparedness training to preparedness primary school age children in the face of the earthquake in the